Immune checkpoint inhibitors related respiratory disorders in patients with lung cancer: A meta-analysis of randomized controlled trials - Liu, Han; Luo, Sean X.; Jie, Jing; Peng, Liping; Wang, Shuai; Song, Lei (Frontiers in Immunology, 2023)
Background In recent years, immune checkpoint inhibitors (ICIs) had extremely rapid growth in anti-cancer and improved outcomes of many malignancies, specifically lung cancer. However, the incidence of ICIs-related adverse events also raised. Using this meta-analysis, ICIs-related respiratory disorders were investigated in lung cancer patients. Methods Using Cochrane Library, Embase, and PubMed databases, we performed an integrated search for randomized controlled trials (RCTs) to compare respiratory disorders among different regimens. The data was prepared with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guideline, and the quality of included studies was evaluated based on the Cochrane manual. Results In total, 22 RCTs were involved in this meta-analysis. Compared with ICIs, chemotherapy reduced the risk of interstitial lung disease (p = 0.03; SMD: 2.81; 95% CI: 1.08, 7.27), pleural effusion (p = 0.002; SMD: 2.12; 95% CI: 1.32, 3.42), and pneumonitis (p < 0.00001; SMD: 9.23; 95% CI: 4.57, 18.64). ICIs plus chemotherapy could provide a higher probability for patients to suffer pneumonitis than chemotherapy (p = 0.01; SMD: 1.96; 95% CI: 1.17, 3.28). In addition, single ICI brought a lower likelihood for patients suffering pneumonitis than double ICIs (p = 0.004; SMD: 2.17; 95% CI: 1.27, 3.69). Conclusion ICIs-based treatment, such as ICIs alone, ICIs plus chemotherapy and double ICIs, can raise the incidences of some respiratory disorders in patients with lung cancer. It suggests that ICIs should be conducted based on a comprehensive consideration to prevent ICIs-related respiratory disorders. To a certain degree, this study might be provided to the clinician as a reference for ICIs practice. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022378901, identifier (CRD42022378901).